Decoupling between chain extension and entanglement via branched structures for ultralow-power biaxially stretched polypropylene capacitor films - Qi Wu; Can Zhao; Enhui Liu; Xuan Wang; Jing Zhou; Rui Han; Min Nie (Chemical Engineering Journal, 2026)

Provenance of CE-6 samples based on ejecta trajectory constraints - Enhui Zou; Shengyi Jin; Teng Hu; Zhizhong Kang; Shuai Shao; Yantong Huang; Dongming Liu; Jinhao Cai; Zhonglu Lei (Planetary and Space Science, 2026)

Microecological trade-offs in partial nitritation under different ammonia-based food-to-microorganism ratios - Junwei Yang; Danyang Zhu; Enhui Xu; Linglong Shi; Rui Liu; Donghai Yang; Yu Hua; Xiaohu Dai (Journal of Environmental Chemical Engineering, 2026)

Dielectric gradient C@SiC@SiO2 microspheres for broadband room-temperature microwave absorption - Zhixiao Wang; Qun Li; Tao Yang; Qiuye Liu; Kang Wang; Enhui Wang; Yanglong Hou; Xinmei Hou (Chemical Engineering Journal, 2026)

2-Hydroxyfluorene triggers a vicious cycle of oxidative stress and gut dysbiosis, leading to intestinal injury in the polychaete Perinereis aibuhitensis - Enhui Liu; Yining Huang; Ziqiao Zhao; Teng Teng; Honglei Zhou; Chune Liu; Feng Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

The Coupling Coordination and Spatio-temporal Evolution of Water-energy-food in the Yellow River Basin - Ken Sun; Xinyu Chen; Jiacheng Liu; Enhui Shi; Yuanbiao Wang; Yiting Zhou; Xiaotong Xing; Jiabin Chen (Water, Air, & Soil Pollution, 2026)

Coupling coordination and spatiotemporal evolution of water and energy welfare performance in 35 cities of the Yellow River Basin, 2010–2019 - Ken Sun; Xiaotong Xing; Jiacheng Liu; Enhui Shi; Yuanbiao Wang; Yiting Zhou; Xinyu Chen (Environment, Development and Sustainability, 2026)

Unveiling the occurrence and ecological risks of phthalate esters in the municipal wastewater treatment plant by a specific fragment-based GC-EI&PCI-HRMS method - Yinuo Xiao; Kun Wang; Jinsong Liu; Jing Wang; Zhengzheng Liu; Qinqin Sun; Chaoming Zhang; Enhui Wu; Jiahui Yang; Baoliang Chen (Water Research, 2026)

Rapid detection of porcine circovirus type2 using a combination of RAA isothermal amplification and Cas12a nucleic detection technology - Lejia Fan; Xueming Liu; Jiaqing Hu; Jinjin Chi; Xiaoyu Fei; Chao Qi; Enhui Wang; Feng Su (Research in Veterinary Science, 2026)

A novel river pattern classification rule based on geometric parameters of channel planform - Zhou Yang; Enhui Jiang; Yanhui Liu; Yuanjian Wang; Wanjie Zhao; Gang Liu (CATENA, 2026)

Microbial Dark Matter, A Multi-layer Mystery - Xiaopan Ma; Enhui Wu; Yuanyuan Guo; Zheng Wei; Qianyi Zhou; Anita Voigt; Yijiang Liu; Xiaotao Shen; Lihui Feng; Shaymaa A. Ismail; Sridhar Mani; Mingguang He; et al. (Phenomics, 2026)

Phosphate removal by CaAlNd LDH/hydroxide composite: Role of synergistic precipitation, coordination, and exchange - Enhui Ji; Biming Liu; Jia Wen; Yuqing Huang; Shuang Dai; Haixia Wu (Journal of Environmental Chemical Engineering, 2026)

Enhanced acetate tolerance and resource recovery via adaptive evolution of Chlorella vulgaris for sustainable upcycling of organic wastewater - Weizhao Meng; Enhui Liu; Jiahao Ma; Yixi Su; Jingyan Hu; Xiaomin Liang; Weiqi Fu (Bioresource Technology, 2026)

Three new species of the diatom genus Epithemia Brébisson ex Kützing (Bacillariophyceae, Rhopalodiales) from Yunnan Province, China - Jiali Ren; Enhui Liu; Yang Liu; Megan Greenwood; Sarah Hamsher; Scott R. Miller; Jingchun Li; Shulian Xie; John Patrick Kociolek; Qi Liu (Journal of Oceanology and Limnology, 2026)

Pulsed electric field technology as a strategy for achieving the synergistic effect of enhancing the safety and flavor quality of egg yolk liquid - Liu Dong; Enhui Ma; Xinqing Lu; Zhijie Bao; Songyi Lin (Food Chemistry, 2026)

Enhanced photodynamic therapy induces dual nuclear/mitochondrial DNA damage and cGAS/STING-driven innate immunity for improved colorectal cancer immunotherapy - Dexiang Zhu; Weijun Huang; Yutong Wang; Yuxiao Yang; Fanghua Su; Chuyue Lu; Zhenyu Lin; Enhui Zhou; Zhian Chen; Ruiyuan Liu; Qianbing Zhang (Chemical Engineering Journal, 2026)

Strengthening coordination for electrolyte diluent via dipole polarization enables rapid Na+ solvation/desolvation kinetics - Yan Meng; Yuanheng Wang; Qingjiang Liu; Xingyu Chen; Enhui Wang; Weihua Chen; Hongji Pan; Jinghao Zhao; Xin Li; Jia-Yan Liang (Chemical Engineering Journal, 2025)

Appraisal and strategic allocation of industrial water use efficiency in henan province: balancing economic and ecological environmental objectives - Ken Sun; Xiaotong Xing; Weisheng Xie; Zhenzhen Yang; Jingmin Han; Yuanbiao Wangas; Jiacheng Liu; Enhui Shi; Jiabin Chen (Environment, Development and Sustainability, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

A multi-attribute decision-making method of cascade reservoir joint scheduling schemes considering water–sediment, eco-environment, and socio-economy in the Yellow River Basin - Donglin Li; Jieyu Li; Yuanjian Wang; Enhui Jiang; Wanjie Zhao; Gang Liu; Zhifeng Yang (Journal of Hydrology, 2025)

Annual multi-objective optimization model and strategy for scheduling cascade reservoirs on the Yellow River mainstream - Gang Liu; Enhui Jiang; Donglin Li; Jieyu Li; Yuanjian Wang; Wanjie Zhao; Zhou Yang (Journal of Hydrology, 2025)

Whole-genome resequencing reveals selection signatures in China's first rainbow trout (Oncorhynchus mykiss) strain “Shuike No. 1” - Haibing Ma; Gaochao Wang; Tianqing Huang; Enhui Liu; Wei Gu; Gefeng Xu (Aquaculture, 2025)

Study on the hydrodynamic mechanics and soil mechanical characteristics under the phenomenon of river-bottom tearing scour (RBTS) - Enhui Jiang; Yanhui Liu; Li Pan; Xianfeng He; Yan Lan; Junhua Li; Yuanjian Wang (Geomorphology, 2025)

Impact of Pacific decadal Oscillation on the extremely cold event frequency in the Taiwan Strait - Yimin Zhang; Yuwu Jiang; Enhui Liao; Wenfang Lu; Yaozhao Zhong; Haowei Sun; Xing Liu; Zhaoyun Wang; Xiaoran Shi (Climate Dynamics, 2025)

Revealing the pivotal role of B/N-co-doping onto carbon nanospheres for promoted sulfamethoxazole degradation and its bio-toxicity evaluation - Jing Wang; Enhui Jiang; Mingyang Jia; Baosong Xing; Chen Fang; Haoqi Wang; Jiaying Yan; Chuanying Pan; Xiang Liu; Xianyong Lan (Journal of Environmental Chemical Engineering, 2025)

Simulations of n-dodecane spray flames in a model gas turbine combustor: Low-temperature chemistry effects - Jinghe Lu; Enhui Liu; Xiao Liu; Chenyang Cao; Shumeng Xie; Shuying Li; Huangwei Zhang (Fuel, 2025)

Processing intensification using porous particles in gas–solid separation fluidized bed - Xibo Liu; Chenyang Zhou; Daohui Lv; Xiaoyang Wei; Chenlong Duan; Enhui Zhou (Chemical Engineering Journal, 2025)

Holographic characterization of typical silicate minerals by terahertz time-domain spectroscopy - Haochong Huang; Xinyu Li; Zhiyuan Zheng; Hanhan Fan; Caiqin Liu; Enhui Yuan; Jialu Gu; Yutong Ma; Qian Xu; Spozmai Panezai; Shanshan Li; Zhuo Zhang; et al. (Applied Clay Science, 2025)

Settlement prediction of a high embankment based on non-linear regression and neural network algorithm - Enhui Yang; Kai Wang; Jinhong He; Kaiwen Liu; Junxin Wang; Haopeng Zhang; Yanjun Qiu (Transportation Geotechnics, 2025)

Spatial confinement of Co-N/O nanocatalyst into hollow carbon nanosphere for water purification and its biotoxicity assessment - Chen Fang; Yangyang Bai; Lingyuan Ma; Yejun Pan; Kun Pang; Jiaying Yan; Jiajun Song; Enhui Jiang; Haiyu Zhao; Chuanying Pan; Xiang Liu; Xianyong Lan (Chemical Engineering Journal, 2025)

Characteristics and Functions of Rhizosphere Bacterial Communities of Camelli sinensis cv. Shifocui with Cold Resistance Characteristics in Anhui Province, China - Shuiqin Shi; Enhui He; Junjie Ma; Mengrui Ge; Jiahui Gao; Tianyi Peng; Yu Fu; Jianfen Wang; Li Gong; Duoqi Zhou; Yafang Liu (Current Microbiology, 2025)

Evaluation of the acute toxic effects of ammonia on juvenile ussuri cisco (Coregonus ussuriensis) based on histopathology, antioxidant enzyme activity, immune response and the integrated biomarker response - Gefeng Xu; Yucai Pan; Wei Gu; Tianqing Huang; Enhui Liu; Gaochao Wang (Marine Pollution Bulletin, 2024)

Factors associated with the distribution of brain metastases in lung cancer: a retrospective study - Yixin Hu; Weiwei Lei; Enhui Xin; Tan Cheng; Jiang Liu; Yu Tang; Yong Lai; Hong Yu; Yong Tan; Jing Yang; Junhao Huang; Daihong Liu; et al. (Clinical & Experimental Metastasis, 2024)

Time-varying parameters of the hydrological simulation model under a changing environment - Ruimin Liu; Ying Luo; Qingrui Wang; Yue Wang; Yue Liu; Xinghui Xia; Enhui Jiang (Journal of Hydrology, 2024)

Renewable hemicellulose-based materials for value-added applications - Guangfu Liao; Enhui Sun; E.B. Gueguim Kana; Hongying Huang; Isaac A. Sanusi; Ping Qu; Hongmei Jin; Jun Liu; Li Shuai (Carbohydrate Polymers, 2024)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

Effects of Exogenous Hormones on Spawning Performances, Serum Gonadotropin and Sex Steroid Hormone in Manchurian Trout (Brachymystax lenok) during Sexual Maturation - Yucai Pan; Gefeng Xu; Tianqing Huang; Wei Gu; Enhui Liu; Gaochao Wang (Fishes, 2024)
The objective of this study was to investigate the effects of salmon gonadotropin releasing hormone analog (S-GnRH-A) and human chorionic gonadotropin (HCG) on the serum levels of gonadotropins (GtHs) and sex steroid hormones in Manchurian trout during sexual maturity. Females in the treatment group were injected with 20 µg/kg S-GnRH-A and 400 IU/kg HCG, whilst males were injected with half the amount. Blood samples were collected at 0, 5, 10, and 20 days post injection (dpi). The results showed an increase in female follicle-stimulating hormone (FSH) levels in the treatment group at 5 dpi, and from 5 dpi onwards, a difference was observed between the groups, with higher FSH levels in the treatment group compared to the control group. In males, FSH levels showed group differences at only 5 dpi (p

Characteristics and influencing factors of greenhouse gas emissions from reservoirs in the Yellow River Basin: A Meta-analysis - Shurui Huang; Peijia Zhang; Wenxiu Zheng; Jiajia Zhang; Yang Li; Yuanjian Wang; Enhui Jiang; Shaoda Liu; Xinghui Xia (Science China Earth Sciences, 2024)

The novel probiotic preparation based on Lactobacillus spp. mixture on the intestinal bacterial community structure of Cherry Valley duck - Shuiqin Shi; Mengrui Ge; Yan Xiong; Yixun Zhang; Wenhui Li; Zhimuzi Liu; Jianfen Wang; Enhui He; Liming Wang; Duoqi Zhou (World Journal of Microbiology and Biotechnology, 2024)

Development of polymorphic simple sequences repeats markers from whole gene resequencing data comparison of 68 Oncorhynchus mykiss - Haibing Ma; Tianqing Huang; Enhui Liu; Gaochao Wang; Wei Gu; Gefeng Xu (Frontiers in Marine Science, 2024)
Rainbow trout ( Oncorhynchus mykiss ) is a significant cold-water fish farmed in China. Currently, most molecular marker-assisted breeding applications in rainbow trout rely on SSR markers. Although many rainbow trout SSR markers have been developed, methods for mining many polymorphic SSR markers from the genome and identifying them efficiently and rapidly are still lacking. For this reason, this study used in silico simulation method to rapidly develop a large number of polymorphic SSR markers quickly. A total of 354,613 SSR loci with two to six nucleotide repeat motifs were mined from 32 chromosomes of the rainbow trout reference genome using GMATA. The chromosome sequences of the reference genome were then aligned to the whole genome sequencing data (10×) of 68 rainbow trout samples. In silico genotyping was performed using the HipSTR programme to compare and count the variation in the number of repeats of the motifs of the SSR loci in the samples. The loci with high deletion rates and monomorphism were discarded, while those with more than one non-reference allele were kept. The final set of polymorphic SSR loci screened was 78,828. Finally, 4,821 SSR loci were selected with more than 3 alleles and no deletion in all rainbow trout samples and were physically mapped. The average polymorphic information content of these loci was 0.692, indicating high levels of polymorphism. These SSRs were utilized to analyse the genetic diversity and population structure of the 68 rainbow trout samples. The results showed that these 68 samples were divided into two groups. These newly discovered polymorphic SSR markers will provide valuable information for evaluating the construction of rainbow trout family lines for genetic diversity and improvement.

How does top-down water unified allocation and regulation decelerate water utilization? Insights from the Yellow River, China - Lingqi Li; Enhui Jiang; Chang Liu; Chong-Yu Xu (Journal of Cleaner Production, 2024)

The effects of swirler vane configurations on the vortex-mixing interaction and combustion stability in a low-emission combustor - Shengnan Li; Xiao Liu; Zhihao Zhang; Guangpu Lv; Enhui Liu; Jinghe Lu; Hongtao Zheng (Fuel, 2024)

Identification and molecular characterization of two liver expressed antimicrobial peptides (LEAPs) in Amur grayling (Thymallus arcticus grubei Dybowski, 1869) - Baorui Cao; Enhui Liu; Tianqing Huang; Wei Gu; Gaochao Wang; Bingqian Wang; Gefeng Xu (Aquaculture, 2024)

The coupling coordination and spatiotemporal evolution of industrial water-energy-CO2 in the Yellow River Basin - Ken Sun; Jingmin Han; Qianru Wu; Weisheng Xie; Wenbo He; Zhenzhen Yang; Yuanbiao Wang; Jiacheng Liu; Enhui Shi (Science of The Total Environment, 2024)

Genome-wide identification of simple sequence repeats and development of polymorphic SSR markers in brown trout (Salmo trutta) - Haibing Ma; Tianqing Huang; Wei Gu; Enhui Liu; Gaochao Wang; Bingqian Wang; Jianshe Zhou; Gefeng Xu (Conservation Genetics Resources, 2023)

Single and joint toxic effects of waterborne exposure to copper and cadmium on Coregonus ussuriensis Berg - Wei Gu; Kai Ji; Tianqing Huang; Enhui Liu; Gaochao Wang; Xiulan Shi; Fulin Dong; Bingqian Wang; Xubin Zhang; Xiance Wang; Gefeng Xu (Ecotoxicology, 2023)

Analysis of flame instability in low-emission tower-type gas turbine combustor with multi-stage methane injection - Enhui Liu; Jinghe Lu; Chenyang Cao; Xiao Liu; Hongtao Zheng; Huangwei Zhang (Fuel, 2023)

Ultra-stable and bifunctional free-standing SiC photoelectrocatalyst for water remediation - Shuang Liu; Tao Yang; Enhui Wang; Hailong Wang; Zhentao Du; Sheng Cao; Qiaobao Zhang; Kuo-Chih Chou; Xinmei Hou (Journal of Cleaner Production, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

Adsorption properties and mechanism of zinc acrylic carbon nanosphere aggregates for perfluorooctanoic acid from aqueous solution - Enhui He; Ning Liu; Yu Zhou; Zheng Wang; Xiaolan Lu; Liangmin Yu (Environmental Pollution, 2023)

Optimization of Ni Co1--Mn Se2 composition for efficient sodium storage - Yumei Liu; Zuguang Yang; Enhui Wang; Quan Kuang; Yong Ming; Benhe Zhong; Zhenguo Wu; Xiaodong Guo (Chemical Engineering Journal, 2023)

PHR1 positively regulates phosphate starvation-induced anthocyanin accumulation through direct upregulation of genes F3’H and LDOX in Arabidopsis - Zhongjuan Liu; Xueqian Wu; Enhui Wang; Yanan Liu; Yi Wang; Qinghua Zheng; Yizhen Han; Zhongze Chen; Yongqiang Zhang (Planta, 2022)

Semisolid Extrusion 3D Printing of Propranolol Hydrochloride Gummy Chewable Tablets: an Innovative Approach to Prepare Personalized Medicine for Pediatrics - Chunxiao Zhu; Yang Tian; Enhui Zhang; Xiang Gao; Hui Zhang; Nan Liu; Xiaolu Han; Yong Sun; Zengming Wang; Aiping Zheng (AAPS PharmSciTech, 2022)

Medium and Long-term Precipitation Prediction Using Wavelet Decomposition-prediction-reconstruction Model - Yongtao Wang; Jian Liu; Rong Li; Xinyu Suo; EnHui Lu (Water Resources Management, 2022)

NaCl-induced expression of AtVHA-c5 gene in the roots plays a role in response of Arabidopsis to salt stress - Aimin Zhou; Enhui Liu; Hongping Ma; Shuang Feng; Shufang Gong; Jingang Wang (Plant Cell Reports, 2018)